PERSONAL GROWTH INITIATIVES IN RELATION TO RECIDIVISM AMONG INMATES AT CLASS IIB STATE DETENTION CENTER PRABUMULIH - Bila, Alisya Salsa; Rohayati, Ade Cici (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to investigate the impact of the Personal Growth Initiative (PGI) on recidivism among repeat offenders at Rutan Class IIB Prabumulih. PGI represents an individual’s conscious effort for active and continuous self-development, which, in the context of corrections, can be a potential approach to reducing recidivism. Using a descriptive qualitative method, data were collected through interviews, observations, and documentation. The findings indicate that the PGI dimensions—readiness for change, planfulness, resource utilization, and intentional behavior—significantly contribute to helping inmates reduce their risk of reoffending. Inhibiting factors such as social stigma and lack of social support delay the rehabilitation process. This study highlights the importance of social support and correctional facilities in strengthening PGI among inmates to reduce recidivism rates. Keywords: Personal Growth Initiative; Recidivism; Prisoners